Manajemen Strategis Madrasah Ibtidaiyah: Perbandingan Antara Madrasah Ibtidaiyah Plus Andalusia Qur’anic School dan Madrasah Ibtidaiyah Al Amanah Kabupaten Bogor - Wening Widhiastuti; Qowaid; Gunawan Anjar Sukmana (Jurnal Dirosah Islamiyah, 2024)
Some madrasas are considered to be of lower quality and less desirable, while other madrasas are competitive and increasingly in demand. One factor that differentiates between the two is the implementation of strategic management in madrasas. This article presents the results of research at two madrasas, namely Madrasah Ibtidaiyah Plus Andalusia Qur'anic School which is relatively high quality and is popular with many students, and Madrasah Ibtidaiyah Al Amanah which is less popular. This research aims to determine and discuss the implementation of strategic management in the two Madrasah Ibtidaiyah, due to the presence or absence of strategic management and the supporting and inhibiting factors in implementing strategic management. The research results show that there is a gradation in the existence of strategic management documents in the two madrasas, from those that are relatively complete to documents that have not been completely written. Madrassas that have more complete strategic management documents produce better quality and public interest compared to madrassas that do not have good strategic management documents. In choosing a madrasa, factors such as the number of students and teachers, facilities, study costs, and individual preferences greatly influence the decisions of parents and students. The limitations of this paper lie in its deeper focus on the comparison between the two madrasas in terms of official documentation, facilities, and tuition fees. This article does not provide an in-depth picture of the quality of graduates and academic results from the two madrasas. Therefore, it can further be enriched by providing further insight into teaching methods, curriculum, or academic achievement to provide a more complete picture of the educational options available.